Illustration of bounded ambiguity. II, The case of the pharmaceutical firm - Alvesson, Mats, 1956- (SAGE knowledge. Cases., 2016)
This case study illustrates the concept of ambiguity in an organization and how it can be bounded. A pharmaceutical firm, Pharma, had a distinct lack of success in its research and development of new products. From interviews with staff, it was clear that there were a number of perceived reasons as to why the new products weren't successful. However, it was clear that many shared the view that more and better management would be the best solution.